Recycling of porous bituminous mixtures - Dias, Teresa (2005)
Once flexible pavements reach minimal bearing capacity, their structural rehabilitation is normally undertaken us ing bituminous mixture overlay. The number of layers and the thickness depend of the existing quality of the pavement and of the required quality determined by the rehabilitation program for a next life period. The rehabilitation of a pavement with a porous bituminous mixture wearing course is usually undertaken without any treatment to increase its bearing capacity. The bearing capacity of this type of mixture can be increased by the use of a grout to fill its voids, increasing its resistance. The new material is produced by spreading a grout over the pavement surface, with the help of rubber scrapers, penetrating the voids of the mixture until it reaches the bottom of the layer. The properties of this material are dependent on void connectivity, in order to allow the grout to flow through them. An adequate viscosity of the grout is essential so as to fill the voids completely. The objective of this paper is to analyse the recycling of porous bituminous mixtures, studying the grout and evaluating new mixture properties in terms of stiffness, fatigue life and permanent deformation.